Analysis of Figurative Language in â€œEasy On Meâ€ Song Lyric - Ni Wayan Swarniti (RETORIKA: Jurnal Ilmu Bahasa, 2022)
It is very interesting to analyze figurative language in a song lyric, because figurative language makes the language more unique by using metaphor, hyperbole, etc. The aim of this research is to classify and analyze the lyric of Adeleâ€™s Song Easy On Me based on figurative language used. This research implies qualitative research. The data source in this research was song lyric of Adeleâ€™s Song entitled Easy On Me. Technique of collecting data in this research was observation. The theory used was from Miller and Greenberg (1981) about figurative language. Each data was analyzed based on the theory of figurative language descriptively. Based on the result of this research, in Comparative Figurative Language, just found data in personification (4 data). In Contradictive Figurative Language, it was found hyperbole (3 data), litotes (2 data), and paradox (1 datum). In Correlative Figurative Language, it was found in this data source, namely: allusion (1 datum), ellipsis (2 data), metonymy (2 data), and symbol (8 data). The most data found in data source was symbol. This song lyric had many figurative languages. It means this song lyric tried to use figurative language to express the feeling or idea imaginatively. In other word, this song lyric tried to create a special image and bring out one's emotions.